Case Management Program on Levels of Fasting Plasma Glucose among Type 2 Diabetes Mellitus Patients - Chaiyarit, Arunee (Journal of The Royal Thai Army Nurses, 2020)
This two-group pre-post/test experimental research aimed to compare levels of fasting plasma glucose between an experimental group and a control group before and after received the case management program for 8 weeks. Sample was 68 type 2 diabetes (DM) patients at an out-patient department of Phraputthabat hospital, Saraburi province. These patients were divided to an experimental group (n=34) and a controlled group (n=34) by using random procedure. An experimental group received the case management program individually that included diet control, medication adherence, alcohol and smoking cessation, exercise, and emotional management from the nurse case managers two hours a week for 8 weeks and monitoring every week by the nurse case manager. A control group received usual care. DM patients were measured for FPG levels at baseline and 8 weeks after experiment. Study data was analyzed using independent t-test procedure. Results showed that the majority of DM patients in a control group was female 67.65% (n= 23). Average age was 65.06 years (SD= 5.92). Average year of diabetes was 9.71 years (SD= 5.95). For an experimental group, the majority was female 67.65% (n= 23). Average age was 64.94 years (SD= 5.11). Average year of diabetes was 10.47 years (SD= 5.28). After DM patients receiving CM program for 8 weeks, levels of FPG in an experimental group was statistically significantly lower than those in a control group at .03